バレンツ海の海氷減少と中緯度大気応答との因果関係について - 佐藤, 和敏; 猪, 上淳; Kazutoshi, Sato; Jun, Inoue (2013)
Abnormal winter sea-ice retreat over the Barents Sea has been considered as a leading clue to the recent mid-latitude severe winters. Barents Sea is considered as a hot spot for the rapid Arctic climate change due to the intense air-sea interaction induced by the sea-ice decrease; however, the underlying mechanisms remain uncertain, in particular causal relation of sea-ice retreat and atmospheric forcing and response. Here we show that the poleward shift of sea surface temperature (SST) over the mid-latitude ocean, where is situated upstream from the Barents Sea, modifies the horizontal distribution of tropospheric heating resulted from change in convection over the warm current, likely acting as a bridge to the Barents Sea by forcing planetary waves. This remote atmospheric response modifies cyclone tracks northwestward, resulting in anomalous warm advection over the Barents Sea sector. Because the southerly winds caused by cyclones blow off the sea ice over the Barents Sea, which is very favorable for establishing the warm Arctic and Siberian cold pattern through the atmospheric response. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object